Cervical ectopic pregnancy – the first case of live birth and uterus-conserving management - Angela Köninger; Buu-Phuc Nguyen; Udo Schwenk; Mehmet Vural; Antonella Iannaccone; Jens Theysohn; Rainer Kimmig (BMC Pregnancy and Childbirth, 2023)
Abstract A 37-old III gravida II para with two previous cesarean sections (CS) presented in 7 + 3 weeks of pregnancy with cervical ectopic pregnancy (CEP). At 12th week of pregnancy, a cerclage was performed to avoid cervical distention by the expanding placenta. Due to missing experience in CEP management and to avoid emergency operation, we recommended CS in 30th week of pregnancy due to unspecific pain of the patient. Vaginal bleeding never occured. After transverse laparotomy, the urinary bladder was sharply dissected from the anterior uterine and cervical wall. The baby was delivered by transverse cervicotomy caudally of the placenta. The placenta was left in situ. The patient then got prophylactic embolization of the uterine arteries to prevent further severe hemorrhage. 48 h later, ultrasound showed a floating, avascular placenta within a poor echogenic fluid-filled cervical space as well as macrohematuria. After re-laparotomy and cervicotomy at the same day, the placenta was completely and easily evacuated. A bladder injury was recognized and closed. We performed a cervical internal os plasty by inverting the cervical lips and suturing their distal ends on the proximal cervical tissue, resulting in complete bleeding cessation. Although, the patient got 8 erythrocyte concentrates at all, she was always in a stable condition without hemorrhagic shock. This case demonstrates for the first time a live-birth with uterus-conserving management in CEP.